AUDIT ATTRIBUTES AND FINANCIAL REPORTING QUALITY OF NIGERIAN DEPOSIT MONEY BANKS: THE MODERATING EFFECT OF GOING CONCERN - Johnson Kolawole OLOWOOKERE; Fatima Imike MBAH; Bolarinwa Rotimi FERUKE; Blessing Onyi AKINDE (Malete Journal of Accounting and Finance, 2024)
The moderating effect of going concern on the influence of audit attributes on the financial reporting quality of listed Nigerian banks was examined in this study. An ex-post facto research design was employed on a population consisting of 23 banks. 13 banks were purposively selected for a period 10 years ranging from 2013-2022. Data used for this study was analyzed using descriptive statistics and structural equation modeling. Audit attributes was proxy with audit fees, audit specialization, audit independence, and audit size while financial reporting quality was measured with discretionary accrual. Going concern was used as the moderating variable. Auditors’ opinion was used to measure going concern. The outcome of the analysis discovered that going concern (β = 0.878, p > 0.634) at 5% level of significance has a positive but insignificant effect on financial reporting quality whereas going concern (β = 0.052, p < 0.028) at 5% level of significance has a positive and significant effect on audit attributes of deposit money banks in Nigeria. Also, all the audit attributes used in this study have a positive and significant effect on financial reporting quality except for audit specialization which has an insignificant relationship with financial reporting quality. The study concluded that audit attributes have a significant effect on financial reporting quality and that going concern has a moderating effect on audit attributes and financial reporting quality. The study recommends that banks should ensure that their going concern ability is being assessed by the external auditor to guarantee the survival of the banks and gain the trust of the investors and shareholders.